Violence against Emergency Nurses in Kermanshah-Iran: Prevalence and Associated Factors - Maryam Janatolmakan; Alireza Abdi; Shahab Rezaeian; Negin Framarzi Nasab; Alireza Khatony (Nursing Research and Practice)
Background. Violence against emergency nurses is a global concern with undesirable physical and psychological consequences. This study was conducted to investigate the characteristics of physical and verbal violence against emergency nurses in Iran. Methods. In this cross-sectional study, 150 nurses working in seven hospitals affiliated to Kermanshah University of Medical Sciences were included in the study using the stratified random sampling method. The data collection tools included a personal information form and a researcher-made questionnaire. Violence-related characteristics were assessed using descriptive statistics. Logistic regression was used to identify factors related to physical and verbal violence. Results. The frequency rates of physical and verbal violence during the past 12 months were equal to 62% (n = 93) and 94.7% (n = 142), respectively. In both types of physical violence (49.5%, n = 46) and verbal violence (40.4%, n = 57), the nursing station was the most common place of violence. In both physical (n = 40, 43.0%) and verbal violence (n = 101, 71.1%), the most common perpetrator was the patient’s family. Most physical violence (57.0%, n = 53) and verbal violence (35.2%, n = 50) occurred in the night shifts. No statistically significant relationship was found between physical and verbal violence and gender, age, marital status, type of employment, and work experience. Discussion. The results indicate the seriousness of workplace violence against nurses. It is necessary to adopt a global approach along with providing sufficient manpower and psychological empowerment of nurses. Further studies with a forward-looking approach are suggested.